Potential coagulation factor changes affecting male regular whole blood donors - Ja'afar, Anis Amira (2017)
The potential health advantages of regular whole blood (WB) donation have been a topic of interest recently related to WB donors. However limited studies are found in Malaysia and elsewhere on this subject. Thus, this study was done primarily to compare selected coagulation factors in male regular and first time WB donors. Assessment of coagulation profile is one way to predict the health advantage of regular donation. Previous study reported reduction in Von Willebrand factor (VWF) following cupping therapy. Similar effect may be seen in regular WB donors which confers protection from cardiovascular disease (CVD) due to haemostatic burden. A comparative cross sectional study was conducted in Hospital Universiti Sains Malaysia Kubang Kerian (HUSM) from December 2014 until April 2016. The participants were Malay male from regular (subject) and first time (control) WB donors. Regular WB donor was defined as a person who routinely donated blood 5 times within the last 2 years. A total of 79 samples were collected and analyzed for coagulation tests such as prothrombin time (PT) and activated partial thromboplastin time (APTT) (as screening test) and others including D-dimer, fibrinogen, Von Willebrand factor (VWF:Ag) and heparin cofactor II (HCII). All the data were analyzed using SPSS software version 23.0. The age of all blood donors ranged between 18 and 54 years old. There was no statistical difference of age between the study and control groups (taken at 50 years old cut off age).The frequency of donation among regular donors showed about 30.8% of them donated more than 20 times (12 out of 39 donors). All the donors showed normal coagulation parameters with mean (SD) of 2.72 (0.59), 0.28 (0.45), 107.04 (32.85), 98.20 (32.86); for fibrinogen, D-dimer, HCII and VWF:Ag respectively. There was a significant, positive and fair correlation between HCII and fibrinogen with r=0.415 and p-value <0.01. The 99th percentiles cut off value for HCII and fibrinogen among the regular donors was lower than first time donors. The 99th percentiles cut off value for vWF:Ag for non-O blood group regular donors was lower than first time non-O donors (196.6% vs 210.2% respectively). Although no statistical different between the mean of coagulation parameters among the two groups, the 99th percentiles cut off value for VWF, HCII and fibrinogen showed a reduction pattern among the regular donors. This finding probably indicate lower haemostatic burden among the regular donors, which may indicate health advantage to this group.